Application of Recombinant DNA Technology (RDT) in Insulin Production as Diabetes Mellitus Therapy: Systematic Literature Review - Marwadani Tajusman; Amelia Putri; Yusmina Hala (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Diabetes mellitus is known as a chronic metabolic disease characterized by impaired insulin production or function, resulting in prolonged hyperglycemia. The availability of safe, effective, and affordable insulin is crucial in managing this disease. Advances in biotechnology through the application of recombinant DNA technology (RDT) have enabled the mass production of human insulin with high purity. This literature review aims to analyze the application of recombinant DNA technology in insulin production and evaluate its contribution as a diabetes mellitus therapy. The method used was a Systematic Literature Review (SLR) of various scientific articles and relevant academic sources discussing genetic engineering processes, microorganism expression systems, and the effectiveness of recombinant insulin through the Scopus database. The results of the study indicate that the technique of inserting the human insulin gene into a plasmid vector and expressing it through microorganisms such as Escherichia coli or yeast allows the production of insulin that is structurally identical to natural human insulin. This technology improves therapeutic safety, reduces the risk of immunological reactions compared to animal-based insulin, and supports the availability of industrial-scale production. The application of recombinant DNA technology plays a significant role in the development of more effective, safe, and sustainable diabetes mellitus therapies.